Water Absorption Of Concrete Contains 5% Of Coconut Shell As Fine Aggregate - Nurliyana Zakirah, Zamri (2023)
Concrete usage is at its highest level right now due to rising demand for construction and development. This is true; concrete has the strength to withstand the pressure being applied to it. The supply or resource of fine aggregate is, however, increasing longer and will eventually run out. Furthermore, after numerous investigations were conducted, the concept to solve this issue by substituting natural waste products like coconut for other resources to be used in concrete emerged. Coconut shell can be used for fine aggregate in this situation. As a result, this study aims to decrease the usage of fine aggregate and increase the use of coconut shell as a replacement. This study shows the results of water absorption and compressive strength conducted on concrete specimens graded 20 N/mm² containing 5% coconut shell in the concrete mix. The duration of concrete curing was tested at 7 and 28 days resulting in a good absorption rate when the coconut shell was immersed first rather than left to dry.